Antisemitic ressentiment-communication directed at RB Leipzig in German football fan culture: the third other - Brunssen, Pavel (Football and discrimination, 2021)
This chapter investigates the ressentiment directed at the club RB Leipzig, which has been widespread in the German football fan culture since the club’s foundation in 2009. In the eyes of those who despise it, RB Leipzig has become the antithesis of a “good” football club and thus an object of ressentiment that goes far beyond criticism of the club’s commercial orientation, and well beyond hostility directed at other clubs. RB Leipzig has become a “subcultural code” that symbolizes the opposite of everything that fans who are doing tradition value. This case study is particularly thought-provoking because RB Leipzig is not addressed as Jewish, but the ressentiment-based forms of communication nevertheless express various antisemitic stereotypes regarding modernity, globalization, and inauthenticity. RB’s enemies identify the club not as an “other” in opposition to one’s own “we” group, but as a decomposing element that threatens all traditional clubs and the game of football itself. It is here that we see antisemitic thinking and feeling intersect with hatred against RB Leipzig.
Gesehen am 28.10.2023